Analysis of Gene Expression Profiles in Leaf Tissues of Cultivated Peanuts and Development of EST-SSR Markers and Gene Discovery. (17th May 2009) - Guo, Baozhu; Chen, Xiaoping; Hong, Yanbin; Liang, Xuanqiang; Dang, Phat; Brenneman, Tim; Holbrook, Corley; Culbreath, Albert
Abstract : Peanut is vulnerable to a range of foliar diseases such as spotted wilt caused by Tomato spotted wilt virus (TSWV), early ( Cercospora arachidicola ) and late ( Cercosporidium personatum ) leaf spots, southern stem rot ( Sclerotium rolfsii ), and sclerotinia blight ( Sclerotinia minor ). In this study, we report the generation of 17, 376 peanut expressed sequence tags (ESTs) from leaf tissues of a peanut cultivar (Tifrunner, resistant to TSWV and leaf spots) and a breeding line (GT-C20, susceptible to TSWV and leaf spots). After trimming vector and discarding low quality sequences, a total of 14, 432 high-quality ESTs were selected for further analysis and deposition to GenBank. Sequence clustering resulted in 6, 888 unique ESTs composed of 1, 703 tentative consensus (TCs) sequences and 5185 singletons. A large number of ESTs (5717) representing genes of unknown functions were also identified. Among the unique sequences, there were 856 EST-SSRs identified. A total of 290 new EST-based SSR markers were developed and examined for amplification and polymorphism in cultivated peanut and wild species. Resequencing information of selected amplified alleles revealed that allelic diversity could be attributed mainly to differences in repeat type and length in the SSR regions. In addition, a few additional INDEL mutations and substitutions were observed in the regions flanking the microsatellite regions. In addition, some defense-related transcripts were also identified, such as putative oxalate oxidase (EU024476) and NBS-LRR domains. EST data in this study have provided a new source of information for gene discovery and development of SSR markers in cultivated peanut. A total of 16931 ESTs have been deposited to the NCBI GenBank database with accession numbers ES751523 to ES768453.